Observation of Single Top Quark Production in Association with a Z Boson in Proton-Proton Collisions at √s=13 TeV; Physical Review Letters; Vol. 122, iss. 13 - Sirunyan A. M.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Asilar E. Ece; Bergauer T. Thomas; Babaev A. A. Anton Anatoljevich; Yuzhakov A. D. Aleksandr Dmitrievich; Okhotnikov V. V. Vitaly Vladimirovich (2019, 2019)
Title screen